RESOLVING ENVIRONMENTAL DISPUTE WITH MEDIATION METHOD - Sabela Gayo (International Asia Of Law and Money Laundering (IAML), 2022)
Dispute the Environment is a dispute between two or more parties that posed the presence or suspected presence of contamination and / or destruction of the environment. Dispute settlement environment in the outer court was held to reach an agreement regarding the form and amount of compensation and/or for specific actions to ensure the will not the occurrence or recurrence of a negative impact on the environment. In the settlement of disputes environment outside the court can use the services of a third party, both of which do not have the authority to take decisions and who has the authority to take decisions, to help resolve disputes environment. Mediation is one form of dispute resolution environment outside the court. In order to resolve the dispute the environment outside the court, then the mechanism is the use of Alternative Dispute resolution as stipulated in Law No. 30 of 1999 on Arbitration and Alternative Dispute resolution. The mediation can also be used to resolve environmental disputes in Court that the mechanism is based on the PERMA No. 1, 2008 on the Procedure of Mediation in the Court